Life quality differences before and after hemorrhoid treatment - Amsriza, Fadli Robby; Fakhriani, Rizka (Intelektual Pustaka Media Utama, 2023)
Hemorrhoids are the third most frequent gastrointestinal condition. The symptoms of hemorrhoid illness may include pain, itching, bleeding, soiling, and swelling. This study aimed to examine the impact of treatment on hemorrhoid patients’ quality of life. 36 patients with hemorrhoids between 18 to 60 took part in this longitudinal study before and after treatment between April and August 2022. Health-related quality of life (HRQOL) before and after treatment is 0.037<0.051. Lower quality of life in terms of essential health is indicated by the health scale modified for hemorrhoid disease symptom score (HSHD) since the score before treatment is lower than the score after treatment. The p-value thus shows a significant impact both before and after treatment. The research on hemorrhoid patients showed that the patient’s quality of life increased after treatment.